Public Water Domain: methodology for its delimitation, basis for its governance (Huellas, 2024)
The shore line is the limit that separates the public water domain from the property of individuals, the criterion for its delimitation is stated by law, both in Argentina and in other countries of the world. But its practical analysis remains a matter of current discussion. In this paper, a geomorphological interpretation of the established criterion is proposed as well as a methodology for its delimitation. To achieve this, different international, national, provincial and papers on shore line works were analyzed, which allowed to establish a criterion adjusted to the natural form of the channel and to cartographically define the shore line by using products of Unmanned Aerial Vehicles (UAVs). If the waterfront is delimited on the basis of natural facts, its indubitable mark on the ground will be close to what actually belongs to the public water domain.